A decision‐making framework for sustainable land use in Hong Kong's urban renewal projects. Issue 1 (2014) - Qiping Shen; Hao Wang; Bo‐sin Tang
<x xml:space="preserve"> Abstract </x> Purpose – Urban renewal projects provide an effective channel for adjusting land‐use allocation and improving land‐use efficiency, which effectively increases land supply. The purpose of this paper is to support the decision‐making process of sustainable land use in urban renewal projects. A GIS‐based framework, consisting of a planning support model and a land information database, has been developed in a typical high‐density city – Hong Kong. Design/methodology/approach – A qualitative and quantitative combined methodology is designed for this research. Several research methods such as expert interviews, focus group meetings, and case studies and technical approaches such as GIS, MCA, and AHP are adopted in this research. Findings – General and sustainability criteria for land‐use decision making in urban renewal along with associated data are identified, and an integrated approach to quantitatively assessing land‐use suitability is developed. Research limitations/implications – The framework was developed in a loosely coupled form rather than a software package installed on a computer, and the development of the land information database was a time‐consuming process as a large amount of data were collected, processed, and analyzed. Originality/value – Application of the proposed framework is reported by showing analyzed results of land‐use suitability. The framework proves a useful tool for both practitioners and researchers involved in sustainable land use for urban renewal. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors wish to express their sincere gratitude to the Department of Building and Real Estate and the Research Institute of Sustainable Urban Development of The Hong Kong Polytechnic University for funding the research project on which this paper is based. Appreciation is also due to Dr. Martyn Hills for his professional text editing and all members of the research team for their invaluable contribution. </ack>